Arbuscular mycorrhiza improved drought tolerance of maize seedlings by altering photosystem II efficiency and the levels of key metabolites - Yanbo Hu; Wei Xie; Baodong Chen (Chemical and Biological Technologies in Agriculture, 2020)
Abstract Background Water shortage can limit plant growth, which can be ameliorated by arbuscular mycorrhizal (AM) symbiosis through physiological and metabolic regulations. Deciphering which physiological and metabolic processes are central for AM-mediated regulations is essential for applications of mycorrhizal biotechnology in dryland agriculture. Methodology In this study, the influence of AM symbiosis on growth performance, photosynthesis, and organ accumulation of key C and N metabolites were assessed by growing maize (Mo17, Lancaster Sure Crop) seedlings inoculated with or without AM fungus (Rhizophagus irregularis Schenck & Smith BGC AH01) under different water regimes in greenhouse. Results Drought stress reduced shoot growth, while AM symbiosis significantly improved growth performances, with significant changes of photochemical processes and organ concentration of the key metabolites. AM symbiosis increased root levels of the metabolites in ornithine cycle and unsaturation of fatty acids regardless of water conditions. Root putrescine (Put) concentration was higher in AM than non-inoculated (NM) plants under well-watered conditions; the conversion of Put via diamine oxidase to γ-aminobutyric acid (GABA) occurred in roots of AM plants under drought stress. Leaf concentration of Put, the tricarboxylic acids, and soluble sugars significantly increased in AM plants under drought stress, showing higher values compared to that of NM plants. Moreover, photosystem II efficiency and chlorophyll concentration were higher in AM than NM plants regardless of water status. Conclusion Fatty acid- and ornithine cycle-related metabolites along with soluble sugars, Put, and GABA were the key metabolites of AM-mediated regulations in response to drought stress.